Design And Simulate The Multimedia And ICT Infrastructure For Computer Man University Campus - Suliman, Ayman Abdel Motti (2004)
This project tries to identify the feasibility for a campus LAN for Campus Man University (CMU) that connects all workstations and servers. A web-enabled information system will be established that will use the LAN to deliver information and share resources.